Green River, running red : the real story of the Green River Killer-- America's deadliest serial murderer - Rule, Ann. (New York : Pocket Star Books, 2005)
Traces the serial murders of the Green River Killer, profiling Gary Ridgway as a happily married man who worked for the same company for thirty years, and discusses the DNA breakthroughs that established his link to the killings.
Originally published: New York : Free Press, 2004.
Keywords: Serial murders -- Washington (State) -- Green River Region (King County) -- Case studies; Ridgway, Gary Leon, -- 1949-; Serial murderers -- Washington (State) -- Green River Region (King County) -- Biography; Rapists -- Washington (State) -- Green River Region (King County) -- Biography